Study on the safety and efficacy of Fu's subcutaneous needling for the treatment of lumbar disc herniation: a systematic review and meta analysis of randomized controlled trials - Liang, Jiao; Zhang, Jin; Zhou, Jie; Yang, Kun; Xiong, Qian (Frontiers in Neurology, 2025)
PurposeSystematic evaluation of the effectiveness and safety of Fu's Subcutaneous Needling (FSN) in the treatment of Lumbar Disc Herniation.MethodsA systematic search was conducted across four Chinese and four English databases, including China National Knowledge Infrastructure (CNKI), Wanfang, China Science and Technology Journal Database (VIP), China Biology Medicine (CBM), PubMed, Cochrane Library, Embase, and Web of Science, to collect randomized controlled trials (RCTs) on the use of Fu's subcutaneous needling for the treatment of lumbar disc herniation published before September 1, 2024. The search was conducted in both Chinese and English, with no restrictions on ethnicity. After rigorous screening of the literature, Meta-analysis was performed using Stata 18.0 and RevMan 5.2.1 software. This study protocol has been registered with the PROSPERO International Prospective Register of Systematic Reviews, with a registration number CRD42024595890.ResultsA total of 17 studies involving 1,467 patients were included. The Meta-analysis results indicated that Fu's subcutaneous needling for lumbar disc herniation was more effective than the control group, with a statistically significant difference. The overall effective rate was: OR = 2.77, 95% CI (1.90, 4.03), Z = 5.31, P < 0.00001. The VAS score was: MD = −1.12,95% CI (−1.35,−0.89),Z = 9.57,P < 0.00001. JOA scores was MD = 4.52, 95% CI (1.83, 7.2), Z = 3.29, P = 0.001.ODI scores with MD = −6.75, 95% CI (−8.42, −5.08), Z = 7.91, P < 0.00001. SF-36 with MD = 8.51, 95% CI (3.64, 13.38), Z = 3.42, P < 0.0006.ConclusionFSN has certain advantages and more safety in the treatment of LDH. However, due to the publication bias, the strength of the evidence is insufficient. High-quality, large-sample, multi-center randomized controlled trials are still needed for further research.Systematic review registrationThe protocol for this systematic review was registered on PROSPERO and is available in full on the website (https://www.crd.york.ac.uk/PROSPERO, CRD42024595890).